Predisposing Factors of Postpartum Depression - Rahmani F; Seyedfatemi N; Asadollahi M; Seyedrasooli A (Iran University of Medical Sciences, 2011)
Background & Aims : Postnatal depression is a major public health problem. With due attention to potential side effects of it on mother and family, determining and reduction of any of the factors can decrease prevalence of this disorder. This study was done to determine the predisposing factors of postpartum depression.   Material & Methods: It was a cross- sectional study with multistage cluster random sampling of 560 women referred to Tabriz health centers 2 mounts after delivery. Data was collected by Edinburgh Postnatal Depression Scale. Data related to demographic characteristics, mother- newborn characteristics and social support was also gathered by a research- made tool. Data was analyzed by SPSS version 16 by using descriptive statistics, Chi square, one way ANOVA, independent T test and logistic regression.   Results: The results of chi square test showed a significant association between mother age, education, illness of mother during pregnancy, type and number of delivery and desired fetal sex and postpartum depression (P<0/05). The results of independent T test also showed a significant relationship between illness of newborn, unplanned pregnancy and postpartum depression (P<0/05). The results of one-way ANOVA indicated that the relation between lack of mother's readiness to accept the responsibility of newborn and husband's feelings about recent pregnancy and postpartum depression was significant (P<0/05). Linear regression showed the most important risk factors of postpartum depression as financial status, educational level, unwanted pregnancy, stress level, newborn illness, and mother's lack of willingness to accept responsibility (p<0.05). Conclusion: Approaches that will lead to increased willingness of mothers to realize the predisposing factors of this disorder, as well as family support and also social support by health care providers can be effective in preventing postpartum depression.